Improving Students' Listening Skill Using Films At The Eleventh Grade Of Sma Negeri 1 Bringin ; Classroom Action Research - Sutanto, Kunang; , Aryati Prasetyarini, S.Pd, M.Pd; , Siti Fatimah, S. Pd, M. Hum (2014)
The general objective of this research is to improve studens' listening skill. While, the specific objectives of this research are, to describe the implementation of listening skill using films, and to identify the improvements of the students' listening ability at SMA 1 Bringin. In achieving the objectives of the research, the researcher uses classroom action research (CAR). Each cycle of the action consists of four steps: planning, acting, observing, and reflecting. The research was held on SMA 1 Bringin Semarang. The subject of this study is (11th class of IPA) students of SMA 1 Bringin that consists of 29 students. The researcher analyzes the data by using interactive analysis and descriptive comparison, the data are observation, documentation, and tests in analyzing the data. There are two cycles in this action research in which each cycle is conducted in two meetings. After analyzing the data, the writer describes the result of the research in which in pre - test of 29 students only 11 students scored 65 and 18 students scored below 65 with the average gra de 42.36. This means mastery 58.82% of students completed the success criteria. Cycle 1 the students who completed is 64.7% and 35.3% did not complete a repair after the implementation of the learning cycle I. Formative test results the second cycle, the level of completeness reaches 100%. The students also show positive responses. They look enthusiastic, energetic, braver, and more confident to listen. Thus, it can be said that the teaching listening to the Eleventh Grade students of SMA 1 Bringin is successfull.